ORGANOLEPTIC ANALYSIS OF SOYBEAN TEMPE WITH THE ADDITION OF SATURATED LEAVES (Saurapus andogynus L): ANALISIS UJI ORGANOLEPTIK TEMPE KEDELAI DENGAN PENAMBAHAN DAUN KATUK (Saurapus andogynus L) - Endiyani; Irhami; Raisatu Nisa (ROCE : Jurnal Pertanian Terapan, 2026)
Tempeh is one of Indonesia’s traditional foods that is now widely available throughout the country and well known internationally. Tempeh is made from soybeans and offers many health benefits because it provides nutrients that support the body’s needs, including protein, fat, carbohydrates, and more. This study aims to determine the effect of adding katuk leaves to soybean tempeh on the organoleptic properties of the resulting product. Data collection and analysis in this study used a completely randomized design (CRD) with katuk leaf concentration as a factor, comprising 4 treatments: T0=0% (control), T1=50%, T2=75%, and T3=100%. Each treatment was repeated 5 times, resulting in 20 experimental units. The results showed that adding katuk leaves to tempeh production had no significant effect on the organoleptic properties of aroma, taste, and texture, but did have a significant effect on color. The highest acceptance by the panelists for tempeh products with katuk leaf addition in terms of color, aroma, taste, and texture was found in treatment T1 = 50% (3.10%) for color, T1=50% (3.10%) for taste, T0=0% (3.02%) for aroma, and T1=100% (3.07%) for texture.